The Environmental Kuznets Curve and Sustainability: A Panel Data Analysis - Sahbi Farhani; Sana Mrizak; Anissa Chaibi; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2014)
In recent years, sustainability has represented one of the most important policy goals explored in the environmental Kuznets curve (EKC) literature. But related hypotheses, performance measures and results continue to present a challenge. The present paper contributes to this ongoing literature by studying two different EKC specifications for 10 Middle East and North African (MENA) countries over the period 1990–2010 using panel data methods. For the first specification, namely EKC, we show that there is an inverted U-shape relationship between environmental degradation and income; while for the second specification, namely modified EKC (MEKC), we show that there is an inverted U-shape relationship between sustainability and human development (HD). The relationships are shaped by other factors such as energy, trade, manufacture added value and the role of law. More interestingly, findings from the estimation show that EKC hypothesis, HD and sustainability are crucial to build effective environmental policies.
Keywords: Q43; Q50; Q56; 330; environmental Kuznets Curve; sustainability; panel data analysis